2011
DOI: 10.1093/abbs/gmr093
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4 is up-regulated by mTOR activation during THP-1 macrophage foam cells formation

Abstract: Macrophage foam cells formation is the most important process in atherosclerotic plaque formation and development. Toll-like receptor 4 (TLR4) is one of the important innate immune sensors of endogenous damage signals and crucial for regulating inflammation. Growing evidence indicates that TLR4 plays a very important role in macrophage foam cells formation. However, the underlying mechanisms regulating TLR4 expression in macrophage are not fully understood. In this study, we induced THP-1 macrophage foam cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 40 publications
1
15
1
Order By: Relevance
“…Moreover, mTOR inhibition during DES transplantation caused endothelial dysfunction and inflammation and promoted thrombus formation31. OxLDL, one of the culprits of atherosclerosis, could active mTOR during THP-1 macrophage foam cells formation and in rabbit femoral SMCs3233. However, we found that oxLDL inhibited mTOR activity in VECs in this study.…”
Section: Discussioncontrasting
confidence: 60%
“…Moreover, mTOR inhibition during DES transplantation caused endothelial dysfunction and inflammation and promoted thrombus formation31. OxLDL, one of the culprits of atherosclerosis, could active mTOR during THP-1 macrophage foam cells formation and in rabbit femoral SMCs3233. However, we found that oxLDL inhibited mTOR activity in VECs in this study.…”
Section: Discussioncontrasting
confidence: 60%
“…49 ox-LDL could active mTOR during the formation of THP-1 macrophage foam cells and in rabbit femoral smooth muscle cells. 50,51 By contrast, a recent report indicates that ox-LDL inhibited mTOR activity in vascular endothelial cells and suggests that the effect of ox-LDL on the mTOR pathway might be cell-type specific. 52 Consistent with the previous study, this study showed that ox-LDL decreased the phosphorylation of mTOR in HUVECs ( Figure 4D).…”
Section: ■ Discussionmentioning
confidence: 92%
“…Therefore, TLR4 might contribute to the progression of atherosclerosis. Furthermore, ox-LDL increased mRNA and protein levels of TLR4 in U937 promonocytic leukemia cells and macrophages [35,36]. We found that ox-LDL increased the expression of TLR4 in cultured mast cells, accompanied by the induction of inflammatory cytokine.…”
Section: Discussionmentioning
confidence: 92%